2000
DOI: 10.1038/sj.leu.2401789
|View full text |Cite
|
Sign up to set email alerts
|

Expression and responsiveness of human interleukin-18 receptor (IL-18R) on hematopoietic cell lines

Abstract: Interleukin-18 (IL-18

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 33 publications
3
39
0
Order By: Relevance
“…IL-18 may mediate its effects directly by augmentation of IFN-γ production 6 10 23 24 or by enhancement of the expression of the IL-12R complex, thereby potentiating the effects of IL-12 25. While many studies have focused attention on the regulation of the IL-12R during Th cell differentiation, fewer have focused on regulation of the IL-18R 24 26 27 28 29. It has been widely assumed that the IL-18Rα is expressed only after T cell activation as the IL-18Rα could readily be detected on fully differentiated murine Th1 cells, but not on Th2 cells, either at the mRNA level or at the cell surface 22 23 24 26.…”
Section: Discussionmentioning
confidence: 99%
“…IL-18 may mediate its effects directly by augmentation of IFN-γ production 6 10 23 24 or by enhancement of the expression of the IL-12R complex, thereby potentiating the effects of IL-12 25. While many studies have focused attention on the regulation of the IL-12R during Th cell differentiation, fewer have focused on regulation of the IL-18R 24 26 27 28 29. It has been widely assumed that the IL-18Rα is expressed only after T cell activation as the IL-18Rα could readily be detected on fully differentiated murine Th1 cells, but not on Th2 cells, either at the mRNA level or at the cell surface 22 23 24 26.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, IL-18 mRNA has been detected in malignant cells from colon and ovarian carcinoma (25, 26), mantle cell lymphoma (27), and skin cancer (28). IL-18R␣ expression has been reported in different hematopoietic cell lines, part of which were derived from patients with lymphoproliferative or myeloproliferative disorders, but not in primary tumor cells (29). EBV infection has been shown to up-regulate IL-18 expression in secondary lymphoid tissues from patients with infectious mononucleosis and, at a lesser extent, posttransplant lymphoproliferative disorder (22).…”
Section: Introductionmentioning
confidence: 99%
“…We have examined these two cell lines with regard to the level of IL-18R␣/␤ expression using flow cytometry and receptor binding assay. Previous data showed that TNF-␣ could significantly increase the response of KG-1 cells to IL-18 in IFN-␥ production, suggesting that TNF-␣ might upregulate the expression of IL-18R␣ and/or IL-18R␤ (18). Therefore, we also analyzed TNF-␣-primed KG-1 cells for receptor expression and IL-18 binding.…”
Section: Expression Of Il-18r␣ and ␤ Subunits And Binding Of Il-18mentioning
confidence: 97%
“…Among the many cell lines tested, L428 exhibited the strongest level of total IL-18 binding, but failed to secret IFN-␥ in response to IL-18 (12,18), and KG-1 cells produced IFN-␥ in response to IL-18 stimulation (18). However the IL-18R expression patterns (i.e., whether they express only IL-18R␣ or both IL-18R␣ and -␤, and the receptor numbers and affinities) on these cells have not been assessed in detail.…”
Section: Expression Of Il-18r␣ and ␤ Subunits And Binding Of Il-18mentioning
confidence: 99%